2017
DOI: 10.1055/s-0042-115932
|View full text |Cite
|
Sign up to set email alerts
|

Psychische Belastung und die Akzeptanz von gewaltlegitimierenden Männlichkeitsnormen bei Jugendlichen

Abstract: The proportion of adolescent migrants in Germany aged 15-20 years has risen to about 29.5% in 2014 according to Federal census statistics. The purpose of the current study was to describe and to compare the psychological strains of adolescent 1 and 2 generation migrants with non-migrants in a representative school survey. Acceptance of violence legitimizing masculinity norms was explored and its correlation with psychological strain was analyzed. Self-reported data of psychological strain (internalizing and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…Although there is evidence that the majority of young immigrants adapt well in their new intercultural setting [ 5 ], research has consistently demonstrated that immigrant adolescents are at increased risk for psychological distress [ 6 9 ], which is particularly the case for 1st generation immigrants [ 10 12 ]. Consistent with the literature, we found in our previous analysis of a representative school survey with 8518 pupils aged 12 to 19 years attending various school types differences in sociocultural and psychological adaptation between adolescents with migration background and their majority peers [ 13 ]. The study showed that 1st generation immigrants scored higher on internalizing and externalizing problems than 2nd generation immigrants or non-immigrants.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Although there is evidence that the majority of young immigrants adapt well in their new intercultural setting [ 5 ], research has consistently demonstrated that immigrant adolescents are at increased risk for psychological distress [ 6 9 ], which is particularly the case for 1st generation immigrants [ 10 12 ]. Consistent with the literature, we found in our previous analysis of a representative school survey with 8518 pupils aged 12 to 19 years attending various school types differences in sociocultural and psychological adaptation between adolescents with migration background and their majority peers [ 13 ]. The study showed that 1st generation immigrants scored higher on internalizing and externalizing problems than 2nd generation immigrants or non-immigrants.…”
Section: Introductionsupporting
confidence: 87%
“…Regardless of immigration background, female adolescents reported more internalizing problems than their male counterparts. No gender difference emerged for externalizing problems [13].…”
Section: Open Accessmentioning
confidence: 84%
See 2 more Smart Citations
“…stellen ein äußerst gelungenes Praxisbeispiel vor, einen Ressourcen orientierten therapeutischen Psychosoziale Versorgung von Geflüchteten Mental Health Services for Refugees Ansatz zur Behandlung von Traumafolgestörungen bei Geflüchteten. Dieser wurde schon bei verschiedenen Gruppen von Flüchtlingen eingesetzt und seine Wirksamkeit bei einer kontrollierten Studie belegt.In der Studie von Klein et al[16] werden Einstellungen von Jugendlichen mit und ohne Migrationshintergrund verglichen und ihre Assoziation zu psychishen Belastungen untersucht.…”
unclassified